Weevils of the genus Neomecopus Hustache, 1921 (Curculionidae: Conoderinae: Mecopini), with description of a new species from the Ryukyus, Japan - Fujisawa, Yusuke; Yoshitake, Hiraku; Kojima, Hiroaki (Zootaxa, 2025)
The previously monotypic weevil genus Neomecopus Hustache, 1921 (Curculionidae: Conoderinae: Mecopini), and the type species N. subarmatus Hustache, 1921 are redescribed; furthermore Neomecopus tamaderai Fujisawa, Yoshitake & Kojima, sp. nov. from Okinawa-jima Is., the Ryukyus, southwestern Japan is described and illustrated. A key to Neomecopus and its related genera is also provided.